PENGARUH LITERASI EKONOMI DAN LINGKUNGAN SOSIAL TERHADAP PERILAKU PEMBELIAN IMPULSIF MELALUI ONLINE SHOP PADA PESERTA DIDIK KELAS X JURUSAN IPS DI SMA NEGERI 8 MAKASSAR - NONENG; TUTI SUPATMININGSIH; INANNA; MUHAMMAD HASAN; MUHAMMAD DINAR (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This study aims to determine the effect of economic literacy skills and the social environment on impulsive buying behavior through online stores. The research method used is research based on a quantitative approach. Methods of data through documentation and questionnaires. The results showed that: the literacy ability of students had no effect on impulsive buying behavior through online stores. In the study, it was also found that there was a positive and significant influence on the social environment on purchasing behavior made through online stores in class X students majoring in social studies at SMA Negeri 8 Makassar. There is a positive and significant effect of collaboration between economic literacy and the social environment on impulsive buying behavior through online stores for class X students majoring in social studies at SMA Negeri 8 Makassar